Terapi Perilaku terhadap Perubahan Perilaku pada Anak dengan Autis - Ni Luh Putu Yunianti Suntari Cakera; Ni Putu Nitasari; Ni Wayan Pebry Arsami; Ni Made Suparmi (Jurnal Gema Keperawatan, 2016)
Purpose this study to determine the influence of behavioral therapy to change behaviors in children with autism in the SLB / A Denpasar District 2016. This study uses one type of non-probability sampling that the saturation sampling or total sampling as many as 22 respondents. Data collected from a sample of the research is the primary data, obtained from the sample studied by using a  questionnaire. Based on the results of research conducted, a total of 12 (54.5%) of respondents have a d Pretest value smaller than the post-test. This illustrates that there is a change in behavior in children after behavioral therapy. The study was conducted on 22 respondents using the technique instruction, response, prompt and rewards